The effects of ingestion of sugarcane juice and commercial sports drinks on cycling performance of athletes in comparison to plain water - Kalpana, K.; Doddipalli, K.; Rishi lal, P.; Lal Khanna, G. (Asian Journal of Sports Medicine, 2013)
Purpose: Sugarcane juice (ScJ) is a natural drink popular in most tropical Asian regions. However, research on its effect in enhancing sports performance is limited. The present investigation was to study the effect of sugarcane juice on exercise metabolism and sport performance of athletes in comparison to a commercially available sports drinks.